Will Poly Ether Ether Ketone Outshine the Existing Dental Materials? - An Overview - Karishma Desai1, Subhabrata Maiti2 , Leslie Rani. S3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
PEEK stands for Poly Ether Ether Ketone.. It is a semi crystalline polycyclic aromatic linear polymer. It is awhite and a radiolucent material that is rigid in nature. PEEK is the latest invention in the field of dentistry.It is known that this material can prove as a substitute for the existing dental materials. It is claimed that thishas better properties than other materials. PEEK has been the center of attention for a lot of scientists lookingfor better alternatives to the existing materials. Various researches and reviews have been carried out in detailto study this material. The role of Poly Ether Ether Ketone in dentistry by itself has been a majorly studiedtopic. A literature review was carried out using a systematic search strategy and articles were found usingkeywords. Literature was taken from databases like PubMed and Google Scholar. Articles that discussed theproperties of PEEK and its applications were included. Other articles which had data regarding the structureand its advantages were also included. This review summarized the properties of Poly Ether Ether Ketone.Its structure, and other applications in different dental materials were also discussed in detail.